2020
DOI: 10.4257/oeco.2020.2401.11
|View full text |Cite
|
Sign up to set email alerts
|

NEW PARASITE OCCURRENCES IN Tamandua tetradactyla (PILOSA: MYRMECOPHAGIDAE) IN THE NORTHEAST OF BRAZIL: A PALEOPARASITOLOGICAL STUDY

Abstract: Paleoparasitological studies have revealed parasite eggs in coprolites from humans and other animals, obtained in archaeological sites in the New and Old World. However, to date, the only parasite found in anteaters coprolites is Gigantorhynchus echinodiscus (Acanthocephala: Gigantorhynchidae). Here we present the results of paleoparasitological analysis of nine Tamandua tetradactyla coprolites, of layers dated from 8,870 and 3,190 years BP, collected in three archaeological sites: Toca dos Coqueiros, Toca da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The egg identified as Nematoda_1 was found in a single sample of caititu and had already been found, in the study region, in the feces of C. thous (Brandão, 2007; Oliveira-Santos, 2013), K. rupestris (Saldanha, 2016), and wild felids (Rosa, 2017). It was also found in coprolites of A. caraya , K. rupestris (Sianto, 2009), and Tamandua tetradactyla (Linneaus, 1758) (Souza et al, 2020). This is the first time it has been found in caititus, and it remains unidentified.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The egg identified as Nematoda_1 was found in a single sample of caititu and had already been found, in the study region, in the feces of C. thous (Brandão, 2007; Oliveira-Santos, 2013), K. rupestris (Saldanha, 2016), and wild felids (Rosa, 2017). It was also found in coprolites of A. caraya , K. rupestris (Sianto, 2009), and Tamandua tetradactyla (Linneaus, 1758) (Souza et al, 2020). This is the first time it has been found in caititus, and it remains unidentified.…”
Section: Discussionmentioning
confidence: 97%
“…In the study region, eggs of Macracanthorhyncus Travassos, 1971, were found in wild cat feces by Rosa (2017). Macracanthorhyncus hirudinaceus was identified by Souza et al (2020) in anteater coprolites up to 8,870 yr old. Swine macracanthorchosis is related to the presence of beetles of the Scarabaeidae family, which have the cystacanth larval form of the parasite, and raising animals in a free manner increases the likelihood of contact with intermediate hosts, favoring infection by this acanthocephala (Nansen and Roepstorff, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the first paleoparasitological studies were focused on the description of infections in ancient humans (Ruffer, 1910;Szidat, 1944), efforts to identify helminths and protozoans in other vertebrate remains throughout the Phanerozoic eon have been noted in the literature. Reports of parasites in fossils and subfossils are uneven, and records from the Cenozoic are by far the most numerous (Araújo et al, 1981;Ferreira et al, 1989bFerreira et al, , 1991Ferreira et al, , 1992Ferreira et al, , 1993Schmidt et al, 1992;Noronha et al, 1994;Jouy-Avantin et al, 1999;Verde & Ubilla, 2002;Sardella & Fugassa, 2009;Beltrame et al, 2011Beltrame et al, , 2012Beltrame et al, , 2013Beltrame et al, , 2015aBeltrame et al, , b, 2017Beltrame et al, , 2018Beltrame et al, , 2022Fugassa et al, 2013Fugassa et al, , 2022McConnell & Zavada, 2013;Wood et al, 2013Wood et al, , 2019Taglioretti et al, 2015;Sianto et al, 2016;Nunes et al, 2017;Perri et al, 2017;Dentzien-Dias et al, 2018;Leles et al, 2018;Tietze et al, 2019Tietze et al, , 2020Souza et al, 2020;Agustín et al, 2021;Cardia et al, 2021;Oyarzún-Ruiz et al, 2021;Petrigh et al, 2021;Sivkova & Kosintsev, 2021;…”
Section: Carmo Et Almentioning
confidence: 99%
“…In Brazil, the first paleoparasitological studies were conducted during the 1970s, by Dr. Luiz Fernando Rocha Ferreira da Silva and Dr. Adauto José Gonçalves de Araújo, from the Instituto Oswaldo Cruz (FIOCRUZ) (Novo & Ferreira, 2016). The identification of parasites in fossils and subfossils of fish, reptiles, birds, and mammals, including humans, from Brazilian lithostratigraphic units, have been presented for the States of Rio Grande do Sul and Santa Catarina (South Region), São Paulo, Minas Gerais and Rio de Janeiro (Southeast Region), Ceará, Piauí and Pernambuco (Northeast Region), and Mato Grosso (Central-West Region) (Figure 1) (Ferreira et al, 1979, 1980, 1983, 1989a, b, 1991, Araújo et al, 1981, 1984, 1989Confalonieri et al, 1981;Noronha et al, 1994;Gonçalves et al, 2003;Sianto et al, 2005Sianto et al, , 2014Sianto et al, , 2016Fernandes et al, 2008;Leles et al, 2008Leles et al, , 2018Lima et al, 2008;Camacho et al, 2013;Dentzien-Dias et al, 2013;Jaeger et al, 2013a, b;Hugot et al, 2014;Silva et al, 2014;Novo et al, 2015;Francischini et al, 2017;Cardia et al, 2018Cardia et al, , 2019aCardia et al, , b, 2021Guedes et al, 2020;Souza et al 2020;Aureliano et al, 2021;Iñiguez et al, 2022;Carmo et al, 2023). Therefore, the present review aimed to access and compile all the scientific publications reporting endoparasites in ancient remains collected in different paleontological and archaeological sites from Brazil, published during ...…”
Section: Carmo Et Almentioning
confidence: 99%